2020
DOI: 10.21608/svuijm.2020.49064.1036
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury in neonatal sepsis: prevalence, and outcome

Abstract: Background: Acute kidney injury (AKI) is an acute and reversible increment in serum creatinine levels regardless of associated or not with a decrease in urine output. AKI is very common among septic neonates. The high mortality among septic neonates with AKI stresses the need for screening them for renal failure. Early recognition of risk factors for AKI may reduce the risk of its occurrence. Objective: This study aimed to evaluate AKI's prevalence and outcome in neonates with neonatal sepsis in our hospital. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Up to 50 % of cases in this research were males. Numerous investigations had demonstrated a male predominance among cases with neonatal sepsis (8,9) . In addition, Higazi et al (10) reported a male preponderance (60 %) in their research of assessment of the diagnostic and prognostic performance of serum amyloid A and urinary interleukin-18 in neonatal sepsis in comparison to CRP.…”
Section: Discussionmentioning
confidence: 99%
“…Up to 50 % of cases in this research were males. Numerous investigations had demonstrated a male predominance among cases with neonatal sepsis (8,9) . In addition, Higazi et al (10) reported a male preponderance (60 %) in their research of assessment of the diagnostic and prognostic performance of serum amyloid A and urinary interleukin-18 in neonatal sepsis in comparison to CRP.…”
Section: Discussionmentioning
confidence: 99%